User authentication using passowrd and hand gesture with leap motion sensor - Chowdhury, Mishkat Haider; Shadman, Qazi; Al Hasan, Sakib; Hassan, Md Adib (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2020.